Analisis Manajemen Aset - Laksono, Moch. Agung; Hidayat, Lukman (LPPM Institut Bisnis dan Informatika Kesatuan, 2018)
Managerial activities in managing the assets of the healthier of course wanted his company could pay its operating needs, be it short term or long term. Therefore, companies need to work out the structure of assets which are qualified to run the company so as not to get caught up in the cash that is not liquid. Sales or profit to the company. The goal of the research is analyzing and critiquing asset management in PT Sumi Indo Wiring Tbk. with a period of 2012-2016 (5 year period) to get performance results against corporate asset management in PT Sumi Indo Wiring Tbk. The results of the Research company showed that companies investing the excess in fixed assets, this is evidenced by the existence of a decrease in Fixed Assets Turn Over from the period 2012-2016. This is an indication that companies are less able to manage the asset sales remains meaningful. and have the increasingly year operating cost increases, this can be proved by the graph of fluctuating operating profit margin especially in the 2012-2013 period has decreased nearly 4%. and although sales rose but could not boost earnings significantly if seen from the graphs of Current asset Turn Over from the period 2012-2016. This decline in decline-experienced company because in terms of managerial less capable of managing his assets. Key Word : Asset Management,Profitability,Liquidity,Activity,Z-Score